2022
DOI: 10.15294/jpii.v11i2.33842
|View full text |Cite
|
Sign up to set email alerts
|

Creative Thinking of Chemistry and Chemistry Education Students in Biochemistry Learning through Problem Based Learning with Scaffolding Strategy

Abstract: The purpose of this study was to describe students' creative thinking skills in a problem-based learning model with scaffolding in the Biochemistry course. This research is mixed method research with an explanatory sequential research design with a sample of 173 students from the study programs of Chemistry Education and Chemistry, Universitas Jambi. In this study, the researchers only used the experimental class. The sampling technique used is total sampling and purposive sampling. Data were collected using o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…The three learning media are electronic-based. It is in line with the development of the millennial generation's needs, namely the use of digital/electronic media (Ernawati et al, 2022). It is also in accordance with the current development of the world of education, namely differentiated learning (Rafi &Pourdana, 2023).…”
Section: Introductionsupporting
confidence: 56%
See 1 more Smart Citation
“…The three learning media are electronic-based. It is in line with the development of the millennial generation's needs, namely the use of digital/electronic media (Ernawati et al, 2022). It is also in accordance with the current development of the world of education, namely differentiated learning (Rafi &Pourdana, 2023).…”
Section: Introductionsupporting
confidence: 56%
“…Learning media must be packaged following technological developments and involve and utilize information and communication technology as facilities to facilitate the learning process (Ernawati et al, 2022;Haristiani & Rifa'i, 2020;Miskiah, Suryono, & Sudrajat, 2019). It is following the demands on education in the 21st century (Fitriyana et al, 2020;Soegoto et al, 2022;Wardani, Lindawati, & Kusuma, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Mixed research, also known as mixed methods research, refers to a research approach that combines elements of quantitative and qualitative approaches in one study. The aim is to leverage the strengths of each approach to provide a more comprehensive understanding of the phenomenon under study [15], [16]. The research design used is sequential explanatory which combines quantitative research followed by qualitative research.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, SUB has no impact on originality. From the coding and SEM analysis results, it can be concluded that reshaping the use of technology in learning with the SAMR Originality is an individual's ability to generate new, unexpected, and unique ideas (Ernawati et al, 2022). The interview results show that some students use Google as a technology to evaluate the originality of their ideas and projects.…”
Section: Originality Based On Samrmentioning
confidence: 98%